2023
DOI: 10.1126/sciadv.adg3527
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying longline bycatch mortality for pelagic sharks in western Pacific shark sanctuaries

Brendan D. Shea,
Austin J. Gallagher,
Lindsay K. Bomgardner
et al.

Abstract: Marine protected areas are increasingly touted for their role in conserving large marine predators such as sharks, but their efficacy is debated. Seventeen “shark sanctuaries” have been established globally, but longline fishing continues within many such jurisdictions, leading to unknown levels of bycatch mortality levels. Using public data from Global Fishing Watch and Regional Fisheries Management Organizations, we quantified longline fishing within eight shark sanctuaries and estimated pelagic shark catch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…A recent study has indicated that mortality rates of blue sharks are very high in shark sanctuaries near the equator (i.e. Federated States of Micronesia, Palau and Marshall Islands; Shea et al, 2023). Therefore, it is necessary to modify or prohibit fishing gears (e.g.…”
Section: Conservation Opportunities For Blue Sharksmentioning
confidence: 99%
“…A recent study has indicated that mortality rates of blue sharks are very high in shark sanctuaries near the equator (i.e. Federated States of Micronesia, Palau and Marshall Islands; Shea et al, 2023). Therefore, it is necessary to modify or prohibit fishing gears (e.g.…”
Section: Conservation Opportunities For Blue Sharksmentioning
confidence: 99%
“…Contrary to these beliefs, as of May 18th, 2023, 27 longline fisheries have been certified as sustainable by the Marine Stewardship Council, with another 15 under assessment (MSC, 2023). Furthermore, although the 17 global shark sanctuaries, serving as specialized Large Marine Protected Areas (LMPA), prohibit shark fishing and trading, many still allow longline tuna and billfish fisheries (Ward-Paige, 2017; Shea et al, 2023). According to Shea et al (2023), who evaluated eight out of 17 existing sanctuaries, shark mortality produced by longline fisheries varied drastically, from 600 in Samoa to 36,256 in the Federated States of Micronesia.…”
Section: Perceptions and Attitudes Toward Longline Fishingmentioning
confidence: 99%
“…Furthermore, although the 17 global shark sanctuaries, serving as specialized Large Marine Protected Areas (LMPA), prohibit shark fishing and trading, many still allow longline tuna and billfish fisheries (Ward-Paige, 2017; Shea et al, 2023). According to Shea et al (2023), who evaluated eight out of 17 existing sanctuaries, shark mortality produced by longline fisheries varied drastically, from 600 in Samoa to 36,256 in the Federated States of Micronesia. Mortality rates in these sanctuaries reached up to 5% of sustainable levels for blue sharks (Prionace glauca), and 40% for silky sharks (Carcharhinus falciformis).…”
Section: Perceptions and Attitudes Toward Longline Fishingmentioning
confidence: 99%
See 2 more Smart Citations